2003
DOI: 10.5014/ajot.57.5.534
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Seating for Children With Attention Deficit Hyperactivity Disorder: Therapy Balls Versus Chairs

Abstract: This study provides evidence that use of therapy balls for students with ADHD may facilitate in-seat behavior and legible word productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 17 publications
1
58
2
1
Order By: Relevance
“…This activates the human proprioceptive and vestibular systems. As Schilling et al 10) found, students appeared to use the stability balls as a form of "self-modulation of personal sensory needs." Movement and physical activity appeared to keep them in their seat and on their task.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This activates the human proprioceptive and vestibular systems. As Schilling et al 10) found, students appeared to use the stability balls as a form of "self-modulation of personal sensory needs." Movement and physical activity appeared to keep them in their seat and on their task.…”
Section: Discussionmentioning
confidence: 99%
“…This result shows that using the therapy ball can increase the ability of the ADHD children to pay attention and decrease the difference between ADHD and normal children. Past research has shown that changing the sitting position can enhance the learning effect for ADHD children 20) and that using a therapy ball can improve in-seat behavior and legible work productivity in them 10) . These changes in behavior have now been verified by EEG and performance approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• Student may attend to classroom instruction for longer periods of time when sensory needs are addressed (Schilling, Washington, Billingsley, & Deitz, 2003).…”
Section: Research Evidence and Related Resources Guiding Practicementioning
confidence: 99%